Production of metal and dielectric films in a combined RF and arc discharge - Gasilin, V.V.; Kunchenko, V.V.; Nezovybat’ko, Yu.N.; Taran, A.V.; Taran, V.S.; Tereshin, V.I.; Shvets, O.M. (Вопросы атомной науки и техники, 2003)
In the presentation we investigate the possibilities to deposit metallic and dielectric films on metal and dielectric materials by means of vacuum technology with application of high frequency (RF) electric fields. As a base-model the device “Bulat-6” was used with proper arc evaporators. The leading-in of a RF power (3 kW, f=1-10 MHz) was realized by connecting the RF generator to a planyclic system of the device. Before the film deposition the samples were conditioned by plasma of RF discharge (without arc discharge) at the gas pressure p=10⁻⁴ Torr. The multi-layer coatings of the type Cr-CrN, Cr-TiN-Cr, Ti-TiN-Ti deposited on complicated shape wares of aluminum alloys had a microhardness value up to 2000 kg/mm². The properties of such coatings were studied depending on the vacuum conditions in the process of deposition. Taking into account the potential well developing under RF field, the experiments were provided on depositing the drip-free coatings by placing the wares in that region of vacuum chamber, which is closed from the direct ingress of particles from the arc vaporizer. The Al₂O₃ and AlN dielectric coatings were obtained and their characteristics were studied by using the electron microscope technique.